2021
DOI: 10.3389/fphys.2021.735932
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Adaptations and Performance Outcomes Following a Step and Exponential Taper in Strength Athletes

Abstract: Before major athletic events, a taper is often prescribed to facilitate recovery and enhance performance. However, it is unknown which taper model is most effective for peaking maximal strength and positively augmenting skeletal muscle. Thus, the purpose of this study was to compare performance outcomes and skeletal muscle adaptations following a step vs. an exponential taper in strength athletes. Sixteen powerlifters (24.0 ± 4.0 years, 174.4 ± 8.2 cm, 89.8 ± 21.4 kg) participated in a 6-week training program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 90 publications
4
28
0
Order By: Relevance
“…Travis et al (33) suggested that given the typically high training loads strength athletes employ (generally $85% 1RM) maintaining or decreasing intensity may be a safer option when constructing a taper for maximal strength. In fact, Travis et al (35) recently demonstrated experimentally that during a taper, training intensity can be reduced by 25% and 1RM performances can be improved in powerlifters. It seems that for weightlifting and athletes in the strength sports, the manipulation of training intensity is quite individualized and may be influenced by a number of variables, including the training load and fatigue going into the taper (15,26), the unique physiological demands (2,7,28,42,44) of the sport, and the associated injury epidemiology (13).…”
Section: When Tapering Did Not Work and Whymentioning
confidence: 99%
“…Travis et al (33) suggested that given the typically high training loads strength athletes employ (generally $85% 1RM) maintaining or decreasing intensity may be a safer option when constructing a taper for maximal strength. In fact, Travis et al (35) recently demonstrated experimentally that during a taper, training intensity can be reduced by 25% and 1RM performances can be improved in powerlifters. It seems that for weightlifting and athletes in the strength sports, the manipulation of training intensity is quite individualized and may be influenced by a number of variables, including the training load and fatigue going into the taper (15,26), the unique physiological demands (2,7,28,42,44) of the sport, and the associated injury epidemiology (13).…”
Section: When Tapering Did Not Work and Whymentioning
confidence: 99%
“…Traditionally, PL research has focused on the exploration of anthropometric characteristics (3,7,8), training (1, 19), and tapering practices (4,15,16,18) of PL athletes. However, there have also been several investigations that have used retrospective results from international and national levels of competition to understand competition outcomes (5,(9)(10)(11)(12)(13)20) better.…”
Section: Introductionmentioning
confidence: 99%
“…Tapering has been extensively examined in relation to endurance sports (8,(16)(17)(18)(22)(23)(24)(25)(26)(27)(28)42) with a growing body of evidence relative to strength sports (3,5,12,21,29,31,32,35,36,38,40,44,45). However, the existing literature examining tapering for maximal strength performance consists primarily of observational research (3,5,12,21,32,35,38,44,45).…”
Section: Introductionmentioning
confidence: 99%